Analisis Kontribusi Retribusi Pelayanan Kesehatan terhadap Penerimaan Retribusi Daerah Kabupaten Batanghari 2017 - Jasasila Jasasila (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
The formulation of the problem in this study is How the Development of Regional Retribution in Batanghari Regency in 2017 and How the Analysis of Contribution of Retribution for Health Services to the Receipt of Regional Retribution in Kabupaten Batanghari in 2017, with the scope of Special Retribution for Parking, Retribution for Health Services and Retribution for Motorized Vehicle Testing. While the purpose of this study was to determine the development of Regional Retribution and Retribution Contributions to Health Services for 2017 Regional Retribution Receipts. The type of data used in this study is a set of information or facts recorded through direct observation while the data used is sourced from the Batanghari Regency Central Bureau of Statistics . From the results of the study, it was found that the Development of Regional Retribution in Batanghari Regency during 2017 experienced fluctuations, the largest development occurred in November 2017, namely 110.18% increase in Regional Retribution from the previous month (October 2017), while the biggest decline occurred in December 2017 where there was a decrease in revenue from Regional Retribution of 57.64% from the previous month (November 2017). During 2017 the average contribution of Retribution for Health Services to Regional Retribution was 76.67%, this shows that Health Service Retribution is the largest source of Retribution in the Regency of Batanghari in 2017